Inclusive Education: Problems and Solutions (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article presents the problems of inclusive learning and solutions for solving them. Among the problems are information on resources and training, teachers and administration, infrastructure and goals, cooperation and the community, as well as through these problems and solutions of inclusive education, creating an effective reading environment for each student and enabling all members of society to read and develop.